Assessment of groundwater quality changes in the aquifers of the Dniprovsko-Donetskyi artesian basin - G. G. Lyutyi (Ukrainian State Geological Research Institute (UkrSGRI), 2021)
According to the Water Framework Directive methodological documents, identification of only two classes of groundwater quality – “good” and “bad”, is provided. Obviously, these two gradations are insufficient for assessing and mapping of water quality changes. Therefore, for this purpose, the approaches defined in the National Standard of Ukraine “Sources of Centralized Drinking Water Supply. Hygienic and Environmental Requirements for Water Quality and Selection Rules” (SSTU 4808:2007), which proposes the division of groundwater in terms of chemical composition into four classes: excellent, good, satisfactory and mediocre, were applied. The article discusses the results of assessing the groundwater quality using an original methodology that allows assessing the quality of groundwater of different age aquifers and at different intervals, as well as predicting the direction of their changes over time. The authors have created hydrogeochemical maps characterizing the quality of the Quaternary aquifer water within the Dniprovsko-Donetskyi artesian basin (DDAB) in different periods of time according to the methodology justified by the National Standard of Ukraine “Sources of Centralized Drinking Water Supply. Hygienic and Environmental Requirements for Water Quality and Selection Rules” (SSTU 4808:2007). To assess changes in the quality of groundwater in time, a comparison of the hydrogeochemical characteristics obtained from the results of the hydrogeological study of groundwater in the course of exploration work in the 60–70s of the last century and the hydrogeological study of the previously mapped areas in 2000–2010 was made. Comparison of data for different periods of time clearly showed the intensive course of the process of groundwater pollution in Quaternary sediments within the DDAB. At the same time, negative tendencies of changes in the quality of groundwaters of more protected – confined aquifers in the Eocene and Lower Cretaceous-Cenomanian sediments for the period from 1970 to 2010 were not detected. The approaches for the cartographic assessment of changes in groundwater quality over time, recommended by SSTU 4808:2007, can be effectively used together with other methods for monitoring groundwater in Ukraine.